From information to knowledge: charting and measuring changes in students' knowledge of a curriculum topic - Ross J Todd (Information Research: An International Electronic Journal)
Introduction. This research sought to investigate how school students build on their existing knowledge of a curriculum topic and transform found information into personal knowledge, and how their knowledge of this topic changes. Method. The qualitative study involved 574 students from Grades 6 to 12 in 10 New Jersey schools. The context for data collection was an instructional programme framed by Kuhlthau's information search process. Analysis. Data were collected through surveys at the initiation, midpoint and conclusion of the instructional programme. The instruments sought to measure changes in knowledge, specifically in relation to substance of knowledge, structure of knowledge, amount of knowledge, estimate of extent of knowledge, and label of knowledge. Results. It was possible to operationalise knowledge change in terms of substance, amount and structure of knowledge, and user-centreed perceptions of knowledge growth. Additive and integrative approaches to knowledge development were identified. Conclusion. Students came to know more about their topics, and perceived that they knew more as they progressed through the task. However, students seemed more oriented to gathering facts and knowing a set of facts, and accumulating these in an additive manner, rather than building complex, integrated and abstract knowledge representations.